Clinical characteristics, surgical management, and prognostic factors for supratentorial hemangioblastoma: A retrospective study - Chen, Long; Xiong, Zujian; Zhou, Yian; Li, Yanwen; Xie, Yuanyang; Xiong, Yi; Wanggou, Siyi; Li, Xuejun (Frontiers in Surgery, 2023)
Background Supratentorial hemangioblastoma is an extremely rare neoplasm. The aim of this study was to delineate the clinical features among cystic and solid supratentorial hemangioblastoma patients and evaluate the risk factors for progression-free survival (PFS). METHODS We conducted a literature search in PubMed for histopathologically identified supratentorial hemangioblastoma between 1947 and 2021, and extracted and collected clinical features of cases treated at our own institute. The rate of PFS was determined using Kaplan-Meier analysis. Differences in categorical factors, including the location of tumor and diagnosis of von Hippel-Lindau (VHL) disease, were analyzed using the Pearson 2 test. Cox regression analysis was performed to evaluate the association between various variates and survival outcomes. RESULTS 237 cases of supratentorial hemangioblastoma were identified from 169 studies. Survival analysis found that patients with cystic tumors had a significantly better prognosis than those with solid tumors (log-rank, p = 0.0122). Cox regression analysis suggested that cystic hemangioblastoma (HR: 0.186, 95% CI: 0.043-0.803, p < 0.05) and GTR (HR: 0.126, 95% CI: 0.049-0.323, p < 0.001) were significant predictors of longer survival (PFS) for supratentorial hemangioblastoma. Analysis of 13 supratentorial hemangioblastoma cases from our institute, we validate that cystic tumor had improved prognosis than solid tumor (log-rank, p = 0.0096) and GTR is superior to STR (log-rank, p = 0.0029). CONCLUSIONS Cystic hemangioblastoma versus solid hemangioblastoma may be two tumoral statuses with different clinical features, and a specific treatment strategy should be considered.